INVESTIGATION OF DOMINANT FREQUENCY AND GROUND AMPLIFICATION BASED ON HVSR MICROTREMOR METHOD IN PANGURURUAN DISTRICT, SAMOSIR - Nasution, Nazaruddin; Sirait, Ratni (EINSTEIN (e-Journal), 2024)
In this study, microtremor wave measurements were carried out using the HVSR (Horizontal to Vertical Spectral Ratio) method to identify earthquake vulnerability in Pangururuan District, Samosir, North Sumatra. In this study, measurements were made at 4 points scattered around the area so that the data obtained represented data in the area. Measurement of signal recording data was carried out for 50-60 minutes for each measurement point. Based on the results obtained, the dominant frequency value of the soil is in the range of 2.29 - 12.78 with a very high classification at points RGR1, RGR3 and RGR4 with type I soil classification, namely hard rock, and point RGR2 is classified as low with type IV soil classification, namely soft soil. While the amplification value in Pangururan District is still classified as a low amplification category with an amplification value of <3.